Use of Benzodiazepines and Haloperidol Among Orthopedic Patients in Postoperative Delirium. A Systematic Review - Szymczak, Mateusz; Iskra-Trifunovic, Joanna; Grzywacz, Anna; Samochowiec, Jerzy; Kolodzie, Lukasz (Current Psychopharmacology, 2014)
Postoperative delirium may occur as a serious complication after orthopedic surgery. In addition, risk factors such as age, mental and organic illnesses may increase the incidence of the aforementioned complication. Delirium has a negative impact on postoperative mobilization and recovery. Furthermore, it may result in longer hospital treatment. This study is a systematic literature review of articles that was conducted through a key word search of PubMed. The review includes: 1) pathogenesis, 2) risk factors in the development of postoperative delirium, and 3) the effective methods and strategies of treatment, especially in relation to patients hospitalized in orthopedics. This systematic review will discuss benzodiazepines and haloperidol, which are used to treat delirium in the prevention and treatment of postoperative delirium. The findings suggest that prevention of postoperative delirium with drugs can be an effective strategy.
Keywords: orthopedic